FUNGSI MUSIK RUWATAN BERSIH DESA DI DESA SIDOREJO KABUPATEN BLITAR - Silvia Nafisatur Rosida; Ananto Sabdo Aji (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2024)
This article entitled "The Function of Ruwatan Bersih Desa Music in Sidorejo Village, Blitar Regency" focuses on the issue of the function of ruwatan bersih desa music in Sidorejo Village. The results show that the village clean ruwatan is held during the harvest season once a year. Ruwatan is believed by the people of Sidorejo Village to prevent the village from danger. The ruwatan procession has requirements, namely time, place, ruwatan actors, properties, and offerings. The structure of the ruwatan ceremony has three parts, namely the opening part, the core part and the closing part. Each music presented also has a function and meaning. Music has an important function in ruwatan bersih desa. There are five prominent functions of music. (1) the entertainment function aims to appreciate culture and liven up the atmosphere. (2) the communication function aims for spiritual communication and message delivery. (3) the symbolic representation function aims for purification symbols, sacred symbols, happiness symbols, and spirit symbols. (4) The function of contribution to cultural continuity and stability aims at tradition-keeping and regeneration. (5) The function of contribution to community integration aims to build togetherness and strengthen social ties.